Semitransparent perovskite solar cell based on ternary cation perovskite light absorption layer and preparation method of semitransparent perovskite solar cell
By adjusting the perovskite components in semi-transparent perovskite solar cells and using ultra-thin metal electrodes, the problem of difficult balance of light transmittance and conversion efficiency in the prior art is solved, and higher light transmittance and stable photoelectric conversion efficiency are achieved.
Patent Information
- Application Number
- CN202510039979.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-10
AI Technical Summary
There are contradictions in existing translucent perovskite solar cells in improving light transmittance and conversion efficiency. The reduction of film thickness leads to weakening of light absorption, and the incomplete coverage of the microstructured perovskite layer leads to a decrease in device stability.
A ternary cationic perovskite absorber layer is used, and the band gap of the material is widened by adjusting the ratio of Br and Cl ions in the perovskite component, thereby improving the light transmittance. At the same time, ultra-thin metal (Au, Cu or Al/Ag) is used as transparent electrodes, and the conductivity is improved and light scattering is reduced through the combination of the nucleation inducing layer and the ultra-thin Ag electrode layer.
The light transmittance and conversion efficiency of translucent perovskite batteries are effectively balanced, avoiding the quality and efficiency problems caused by reduced film thickness and incomplete coverage, and improving the stability and conductivity of the battery.
Smart Images

Figure CN119894215A_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of perovskite solar cells, and in particular to a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer and a preparation method thereof. [Background technology]
[0002] In recent years, perovskite solar cells have attracted great attention from researchers in the photovoltaic field due to their excellent optoelectronic properties and potential cost advantages. A major research direction in the photovoltaic field is semi-transparent solar cells. It is a type of cell that allows partial visible light to pass through (partial visible light absorption), and has the advantages of both lighting and power generation. It can be used on car roofs, windows of buildings and skyscrapers to provide a continuously charged power source for the car body and provide shading and clean energy for buildings. It is worth noting that due to the high light absorption coefficient and adjustable band gap of perovskite materials, this type of cell can also be semi-transparent, becoming another hot spot in the field of scientific research. Generally speaking, efficiency and transmittance are the two most important indicators for evaluating semi-transparent solar cells. However, more visible light transmission means less light absorption in the photosensitive layer of the device in this band. Therefore, efficiency and transmittance are also contradictory. It can be seen that how to balance the absorption of the photosensitive layer and the transmittance of the overall device is the key to the design of this type of device. At present, the semi-transparency of perovskite solar cells is generally achieved by making the perovskite light-absorbing layer very thin. For example, Yuan et al. reduced the concentration of the perovskite precursor, and the thickness of the corresponding film was reduced from 300nm to 150nm. A semi-transparent cell based on a 150nm thick photosensitive layer achieved a photoelectric conversion efficiency of 10.83% and an average visible light transmittance of 21% (Journal of Materials Chemistry A, 2018, 6(40): 19696-19702). However, when the film thickness decreases, the quality of the film also deteriorates, and it will be difficult to obtain a dense and uniform film. At the same time, as the defects of the film body increase, the stability of the device also deteriorates. Another method for semi-transparency of perovskite solar cells is to prepare a microstructured perovskite photosensitive layer, that is, to partially cover the perovskite film in the light-absorbing layer, and make the area not covered by the perovskite completely transparent, providing a path for light to pass through, thereby achieving semi-transparency. For example, Eperon et al. from Oxford University used a dewetting method to prepare an island-structured perovskite layer. The thickness of the "island" formed by the perovskite is sufficient to absorb all visible light, while the area without perovskite coverage is transparent, ultimately achieving a photoelectric conversion efficiency of 3.5% and an average visible light transmittance of 30% (ACS Nano, 2014, 8(1): 591-598). However, this method will cause direct contact between the electron transport layer and the hole transport layer in the area without perovskite coverage, forming a short circuit, thereby exacerbating the recombination of photogenerated carriers. In addition, in the selection of electrodes for semi-transparent perovskite cells, transparent oxides or metal nanowires are often used as electrode materials (Nanoscale, 2015, 7(5): 1642-1649), but transparent oxides as electrodes of batteries will result in large contact resistance between batteries, and although metal nanowires have good conductivity, the high junction resistance between them limits their overall conductivity.Therefore, using these materials as transparent electrodes remains a major challenge in the preparation of high-efficiency semi-transparent perovskite cells.
[0003] In summary, in the existing methods for preparing semi-transparent perovskite solar cells, although a semi-transparent light-absorbing layer can be prepared by reducing the thickness, the reduction in film thickness is accompanied by a reduction in light absorption, and there are still many difficulties in preparing a uniform, hole-free, and defect-free ultra-thin perovskite light-absorbing layer. Although the preparation of a micro-nanostructured perovskite layer does not require the control of the film thickness, the photoelectric conversion efficiency of the battery will decrease as the coverage decreases due to the incomplete coverage of the film. At the same time, the exposed area also forms a photogenerated carrier recombination center, which affects the performance of the device. Therefore, these two methods for preparing semi-transparent perovskite cells are not perfect. [Summary of the invention]
[0004] One of the technical problems to be solved by the present invention is to provide a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer, which improves the transmittance of the perovskite light-absorbing layer and the metal electrode and the conductivity of the metal electrode, thereby effectively balancing the transmittance and conversion efficiency of the semi-transparent perovskite cell.
[0005] The present invention achieves one of the above-mentioned technical problems by:
[0006] A semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer, wherein the semi-transparent perovskite solar cell is provided with a conductive glass, a NiO hole transport layer, a SAM hole transport layer, a Cs 0.05 FA 0.85 MA 0.1 PbI x Br 3-x Perovskite light absorbing layer, PCBM electron transport layer, BCP interface modification layer and metal electrode, wherein 0<x<3;
[0007] The Cs 0.05 FA 0.85 MA 0.1 PbI x Br 3-x The preparation method of the perovskite light-absorbing layer is as follows: a certain amount of PbI2, PbBr2, FAI, MAI, and CsI are dissolved in a mixed solution of DMF and DMSO, and the molar ratio of each component is (PbI2+PbBr2): FAI: MAI: CsI is 1.7115:1.3855:0.163:0.0815; then 9 mol% of MACl is added as an additive; then the perovskite precursor solution is obtained by rotating and stirring until the drug is completely dissolved; finally, the solution is spin-coated on the surface of the substrate, and then annealed at a temperature of 80-120°C to obtain Cs0.05 FA 0.85 MA 0.1 PbI x Br 3-x Perovskite light absorbing layer;
[0008] The metal electrode comprises a nuclear induction layer and an Ag electrode layer. The nuclear induction layer is made of Au, Cu or Al and has a thickness of 0.5 to 1 nm. The thickness of the Ag electrode layer is 7 to 16 nm.
[0009] Furthermore, the conductive glass is ITO conductive glass, the thickness of the ITO conductive glass is 350-450nm, the thickness of the NiO hole transport layer is 10-30nm, the thickness of the SAM hole transport layer is 5-10nm, the thickness of the perovskite light absorption layer is 70-200nm, the thickness of the PCBM electron transport layer is 10-30nm, and the thickness of the BCP interface modification layer is 1-5nm.
[0010] Furthermore, the volume ratio of DMF:DMSO is 4:1.
[0011] Furthermore, the Cs 0.05 FA 0.85 MA 0.1 PbI x Br 3-x x=1.5 in the perovskite light absorbing layer.
[0012] Furthermore, the concentration of the perovskite precursor solution is 1.63 M, wherein the PbI2 is in excess of 5 mol%.
[0013] One of the technical problems to be solved by the present invention is to provide a method for preparing a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer, which improves the transmittance of the perovskite light-absorbing layer and the metal electrode and the conductivity of the metal electrode, thereby effectively balancing the transmittance and conversion efficiency of the semi-transparent perovskite cell.
[0014] The present invention achieves the second of the above technical problems in this way:
[0015] A method for preparing a semi-transparent perovskite solar cell based on a ternary cation perovskite light absorbing layer, wherein the semi-transparent perovskite solar cell structure is a semi-transparent perovskite solar cell based on a ternary cation perovskite light absorbing layer as claimed in any one of claims 1 to 2, and the method steps are as follows:
[0016] 1) Spin coating a NiO hole transport layer on the treated ITO conductive glass;
[0017] 2) The substrate is moved into a glove box and then spin-coated with a SAM hole transport layer;
[0018] 3) Spin coating the perovskite film, spin coating the prepared perovskite precursor solution on the substrate, using a multi-step spin coating method, and annealing at 80-120°C after the spin coating is completed; the preparation method of the perovskite precursor solution is: dissolving a certain amount of PbI2, PbBr2, FAI, MAI, and CsI into a mixed solution of DMF and DMSO, and the molar ratio of each component is (PbI2+PbBr2): FAI: MAI: CsI is 1.7115:1.3855:0.163:0.0815; then adding 9 mol% MACl as an additive; then rotating and stirring until the drug is completely dissolved to obtain a perovskite precursor solution;
[0019] 4) Spin coating to prepare PCBM electron transport layer;
[0020] 5) Spin coating to prepare BCP interface modification layer;
[0021] 6) Evaporation of transparent electrode: First, slowly evaporate 1nm of Au, Cu or Al as a nucleation induction layer, and then evaporate 7-16nm ultra-thin Ag electrode layer.
[0022] Furthermore, the preparation method is specifically as follows:
[0023] 1) Spin-coat the NiO hole transport layer on the treated ITO conductive glass at a speed of 3000 rpm / s for 20 seconds. After spin coating, place the solution on a constant temperature heating table and heat it in air at 140°C for 10 minutes; wherein, the NiO solution is prepared by dissolving NiO nanoparticles in deionized water at a concentration of 10 mg / ml;
[0024] 2) Move the substrate into the glove box, and then spin-coat the SAM hole transport layer at a speed of 4000 rpm / s for 30 seconds. After spin coating, place it on a constant temperature heating table and heat it at 100°C for 10 minutes; the SAM solution is prepared by dissolving Me-4PACz nanoparticles in ethanol at a concentration of 0.5 mg / ml;
[0025] 3) Spin coating the perovskite film. Before spin coating the perovskite film, filter the dissolved perovskite precursor solution with a 0.2 μm PTFE filter;
[0026] The prepared perovskite precursor solution was spin-coated on the substrate using a multi-step spin-coating mode. In the first step, the rotation speed was adjusted to 1000rpm / s and the spin coating was performed for 10s. In the second step, the rotation speed was 5000rpm / s and the spin coating was performed for 40s. During the second step of spin coating, 250μL of anti-solvent chlorobenzene was added using a pipette when there were 10s of spin coating time left. After the spin coating was completed, the solution was annealed on a heating table at 100°C for 30min. The perovskite precursor solution was prepared by dissolving a certain amount of PbI2, PbBr2, FAI, MAI and CsI into a mixed solution of DMF and DMSO, and the molar ratio of each component was (PbI2+PbBr2): FAI: MAI: CsI was 1.7115:1.3855:0.163:0.0815. Then, 9mol% of MACl was added as an additive. The solution was then rotated and stirred until the drug was completely dissolved to obtain a perovskite precursor solution.
[0027] 4) Prepare the PCBM electron transport layer by spin coating at a speed of 1500 rpm / s and a spin coating time of 30 seconds. Then heat at 100°C for 5 minutes. The solution preparation method of the PCBM electron transport layer is as follows: dissolve the PCBM nanoparticles in 1 mL of chlorobenzene to a concentration of 20 mg / mL;
[0028] 5) Spin coating to prepare the BCP interface modification layer, the rotation speed is 5000 rpm / s, the spin coating time is 30 s, and the dynamic spin coating method is adopted; then it is heated at 100°C for 3 min; wherein the solution preparation method of the BCP interface modification layer is: dissolving the BCP nanoparticles in isopropanol solution at a concentration of 0.5 mg / mL, and taking the upper clear liquid for use;
[0029] 6) Evaporating a transparent electrode: first, slowly evaporate 1 nm of Au, Cu or Al at a speed of 0.01 nm / s as a nucleation induction layer, and then evaporate 7-16 nm of an ultra-thin Ag electrode layer at a speed of 0.05 nm / s.
[0030] Furthermore, the volume ratio of DMF:DMSO is 4:1.
[0031] Furthermore, the concentration of the perovskite precursor solution is 1.63 M, wherein the PbI2 is in excess of 5 mol%.
[0032] The present invention has the following advantages:
[0033] The present invention regulates the light transmittance of the film from the perspective of regulating the perovskite components, that is, in the ternary cation perovskite (Cs 0.05 FA 0.85 MA 0.1PbI3) is doped with a certain amount of Br and Cl to widen the band gap of the material, thereby achieving more visible light transmission. At the same time, by changing the ratio of I:Br or I:Br:Cl ions in the perovskite component, perovskite films with different transmittances can be further achieved. The invention realizes the semi-transparency of the perovskite battery from the perspective of the essential properties of the material, avoids the problems of reduced quality of the perovskite light-absorbing layer and reduced device efficiency caused by reduced film thickness and incomplete film coverage, and effectively balances the transmittance and conversion efficiency of the semi-transparent perovskite battery. In addition, compared with transparent oxides or metal nanowires as transparent electrodes, the present invention uses ultra-thin metals (Au, Cu or Al / Ag) as transparent electrodes. By first depositing 1nm of Au, Cu or Al as a nucleation induction layer, the particle size of the ultra-thin silver electrode is reduced by the strong adhesion between Au, Cu or Al and Ag, thereby obtaining a uniform and continuous high-quality ultra-thin silver electrode. The electrode effectively reduces light scattering and has a high electrical conductivity. It also maintains the photoelectric conversion efficiency of the battery well while achieving a certain transmittance.
Brief Description of the Drawings
[0034] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0035] Figure 1 This is a layered structure diagram of a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer according to the present invention.
[0036] Figure 2 The different contents of Br in the embodiments of the present invention - Absorption spectrum of the doped perovskite absorber layer.
[0037] Figure 3 The different contents of Br in the embodiments of the present invention - Transmission spectrum of the doped perovskite absorber layer.
[0038] Figure 4 Schematic diagram of light transmittance comparison between a comparative metal electrode (Ag) with different thicknesses in an embodiment of the present invention and a metal electrode (Cu / Ag) of the present invention.
[0039] Figure 5 This is a comparison chart of the transmittance of the semi-transparent perovskite solar cell according to an embodiment of the present invention and the solar electrode of a reference group. [Specific implementation method]
[0040] The following will be combined with the attached Figure 1-5The technical scheme of the present invention is clearly and completely described in detail with specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0041] Example
[0042] 1. Preparation method:
[0043] 1) First, place the ITO conductive glass in an ultrasonic bath and clean it with conductive glass cleaning liquid, deionized water, acetone, and ethanol for 15 minutes respectively, then blow it dry with a nitrogen gun and place it in a UV ozone machine for 15 minutes; spin-coat the NiO hole transport layer on the treated ITO conductive glass at a speed of 3000rpm / s and a spin-coating time of 20s. After spin-coating, place it on a constant temperature heating table and heat it in air at 140℃ for 10 minutes; wherein, the preparation method of the NiO solution is: dissolve NiO nanoparticles in deionized water at a concentration of 10mg / ml;
[0044] 2) Move the substrate into the glove box, and then spin-coat the SAM hole transport layer at a speed of 4000 rpm / s for 30 seconds. After spin coating, place it on a constant temperature heating table and heat it at 100°C for 10 minutes; the SAM solution is prepared by dissolving Me-4PACz nanoparticles in ethanol at a concentration of 0.5 mg / ml;
[0045] 3) Spin coating the perovskite film. Before spin coating the perovskite film, filter the dissolved perovskite precursor solution with a 0.2 μm PTFE filter;
[0046] The prepared perovskite precursor solution was spin-coated on the substrate using a multi-step spin-coating mode. In the first step, the rotation speed was adjusted to 1000 rpm / s and the spin coating was performed for 10 seconds. In the second step, the rotation speed was adjusted to 5000 rpm / s and the spin coating was performed for 40 seconds. During the second step of spin coating, 250 μL of anti-solvent chlorobenzene was added using a pipette when there were 10 seconds left in the spin coating time. After the spin coating was completed, the solution was annealed on a heating table at 100°C for 30 minutes. The preparation method of the perovskite precursor solution was as follows: a certain amount of PbI2, Pb Br2, FAI, MAI, and CsI are dissolved in a mixed solution of DMF and DMSO, and the molar ratio of each component is (PbI2+PbBr2): FAI: MAI: CsI is 1.7115:1.3855:0.163:0.0815; then 9 mol% MACl is added as an additive; then the mixture is rotated and stirred until the chemicals are completely dissolved to obtain a perovskite precursor solution; the concentration of the perovskite precursor solution is 1.63M, of which PbI2 is in excess of 5 mol%.
[0047] 4) Prepare the PCBM electron transport layer by spin coating at a speed of 1500 rpm / s and a spin coating time of 30 seconds. Then heat at 100°C for 5 minutes. The solution preparation method of the PCBM electron transport layer is as follows: dissolve the PCBM nanoparticles in 1 mL of chlorobenzene to a concentration of 20 mg / mL;
[0048] 5) Spin coating to prepare the BCP interface modification layer, the rotation speed is 5000 rpm / s, the spin coating time is 30 s, and the dynamic spin coating method is adopted; then it is heated at 100°C for 3 min; wherein the solution preparation method of the BCP interface modification layer is: dissolving the BCP nanoparticles in isopropanol solution at a concentration of 0.5 mg / mL, and taking the upper clear liquid for use;
[0049] 6) Evaporation of transparent electrode: first, slowly evaporate 1nm Cu at a speed of 0.01nm / s as a nucleation induction layer, and then evaporate 7-16nm ultra-thin Ag electrode layer at a speed of 0.05nm / s. 0.05 FA 0.85 MA 0.1 PbI x Br 3-x / PCBM / BCP / Au / Ag structured semi-transparent perovskite solar cells.
[0050] Among them, the thickness of the ITO conductive glass is 450nm, the thickness of the NiO hole transport layer is 30nm, the thickness of the SAM hole transport layer is 10nm, the thickness of the perovskite light absorption layer is 200nm, the thickness of the PCBM electron transport layer is 30nm, and the thickness of the BCP interface modification layer is 5nm.
[0051] 2. Performance Testing
[0052] The structure diagram of the device is as follows Figure 1 As shown, for different contents of Br - The performance of the doped perovskite light absorbing layer and the Ag electrode layer of different thicknesses was tested. For details, please refer to Figure 2-5 , and Table 1.
[0053] Figure 2 Different content of Br - The absorption spectrum of the perovskite absorption layer doped with (i.e., the amount of PbBr2 substance / (the amount of PbI2 substance + the amount of PbBr2 substance)) is shown in Figure 2. Figure 2 It can be seen that the band gap of the perovskite light absorption layer increases with the increase of the content of doped Br ions ( Figure 2 ), and the transmittance of the perovskite film increases significantly with the increase of Br ion content ( Figure 3 ). Figure 4 1 is a schematic diagram comparing the transmittance of the comparative metal electrodes (Ag) with different thicknesses and the metal electrodes (Cu / Ag) of the present invention, and Table 1 is a comparison of the average transmittance and sheet resistance parameters of the comparative metal electrodes (Ag) with different thicknesses and the metal electrodes (Cu / Ag) of the present invention. It can be seen from the figure that under the premise of the same thickness of the Ag electrode, the metal electrode (Cu / Ag) of the present invention has higher transmittance and lower sheet resistance. Figure 5 The transmittance comparison diagram of the semi-transparent perovskite solar cell of the present invention and the reference group solar cell, wherein the perovskite absorption layer of the semi-transparent perovskite solar cell of the present invention is a 50% Br - The doped perovskite absorber layer and metal electrode are 1nm Cu / 10nmAg, and the perovskite absorber layer of the reference group is Cs 0.05 FA 0.85 MA 0.1 PbI3, the metal electrode is 130nmAg, and the other layer structures are the same as the present invention. It can be seen from the figure that the light transmittance of the semi-transparent perovskite solar cell of the present invention is higher than that of the reference group. The average visible light transmittance of the present invention is calculated to be 15.4%, which is better than 7.71% of the reference group. At the same time, the photoelectric conversion efficiency of the cell of the present invention is 15.9%, while that of the reference group is 16.5%, and the efficiency has not been significantly reduced.
[0054] Table 1 Average transmittance and sheet resistance of electrodes with different thicknesses
[0055]
[0056] It can be seen that compared with the prior art, the present invention realizes the semi-transparency of perovskite cells from the perspective of material component regulation, avoiding the problems of reduced quality of the perovskite light-absorbing layer and reduced device efficiency due to reduced film thickness and incomplete film coverage; combining ultra-thin metal Au / Ag as transparent electrodes further reduces light scattering, while ensuring a lower series resistance of the cell, thereby effectively balancing the transmittance and conversion efficiency issues of semi-transparent perovskite cells.
[0057] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer, characterized in that: The semi-transparent perovskite solar cell is provided with conductive glass, NiO hole transport layer, SAM hole transport layer, Cs 0.05 FA 0.85 MA 0.1 PbI x Br 3-x Perovskite light absorption layer, PCBM electron transport layer, BCP interface modification layer and metal electrode, wherein 0<x<3; The Cs 0.05 FA 0.85 MA 0.1 PbI x Br 3-x The preparation method of the perovskite light-absorbing layer is as follows: a certain amount of PbI2, PbBr2, FAI, MAI, and CsI are dissolved in a mixed solution of DMF and DMSO, and the molar ratio of each component is (PbI2+PbBr2): FAI: MAI: CsI is 1.7115:1.3855:0.163:0.0815; then 9 mol% of MACl is added as an additive; then the perovskite precursor solution is obtained by rotating and stirring until the drug is completely dissolved; finally, the solution is spin-coated on the surface of the substrate, and then annealed at a temperature of 80-120°C to obtain Cs 0.05 FA 0.85 MA 0.1 PbI x Br 3-x Perovskite light absorbing layer; The metal electrode comprises a nuclear induction layer and an Ag electrode layer. The nuclear induction layer is made of Au, Cu or Al and has a thickness of 0.5 to 1 nm. The thickness of the Ag electrode layer is 7 to 16 nm.
2. A semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer according to claim 1, characterized in that: The conductive glass is ITO conductive glass, the thickness of the ITO conductive glass is 350-450nm, the thickness of the NiO hole transport layer is 10-30nm, the thickness of the SAM hole transport layer is 5-10nm, the thickness of the perovskite light absorption layer is 70-200nm, the thickness of the PCBM electron transport layer is 10-30nm, and the thickness of the BCP interface modification layer is 1-5nm.
3. A semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer according to claim 1, characterized in that: The volume ratio of DMF:DMSO is 4:
1.
4. A semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer according to claim 1, characterized in that: The Cs 0.05 FA 0.85 MA 0.1 PbI x Br 3-x x=1.5 in the perovskite light absorbing layer.
5. A semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer according to claim 1, characterized in that: The concentration of the perovskite precursor solution is 1.63 M, with an excess of 5 mol% PbI2.
6. A method for preparing a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer, characterized in that: The semi-transparent perovskite solar cell structure is a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer as claimed in any one of claims 1 to 2, and the method steps are as follows: 1) Spin coating a NiO hole transport layer on the treated ITO conductive glass; 2) The substrate is moved into a glove box and then spin-coated with a SAM hole transport layer; 3) Spin coating the perovskite film, spin coating the prepared perovskite precursor solution on the substrate, using a multi-step spin coating method, and annealing at 80-120°C after the spin coating is completed; the preparation method of the perovskite precursor solution is: dissolving a certain amount of PbI2, PbBr2, FAI, MAI, and CsI into a mixed solution of DMF and DMSO, and the molar ratio of each component is (PbI2+PbBr2): FAI: MAI: CsI is 1.7115:1.3855:0.163:0.0815; then adding 9 mol% MACl as an additive; then rotating and stirring until the drug is completely dissolved to obtain a perovskite precursor solution; 4) Spin coating to prepare PCBM electron transport layer; 5) Spin coating to prepare BCP interface modification layer; 6) Evaporation of transparent electrode: First, slowly evaporate 1nm of Au, Cu or Al as a nucleation induction layer, and then evaporate 7-16nm ultra-thin Ag electrode layer.
7. A method for preparing a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer according to claim 6, characterized in that: The preparation method is specifically as follows: 1) Spin-coat the NiO hole transport layer on the treated ITO conductive glass at a speed of 3000 rpm / s for 20 seconds. After spin coating, place the solution on a constant temperature heating table and heat it in air at 140°C for 10 minutes; wherein, the NiO solution is prepared by dissolving NiO nanoparticles in deionized water at a concentration of 10 mg / ml; 2) Move the substrate into the glove box, and then spin-coat the SAM hole transport layer at a speed of 4000 rpm / s for 30 seconds. After spin coating, place it on a constant temperature heating table and heat it at 100°C for 10 minutes; the SAM solution is prepared by dissolving Me-4PACz nanoparticles in ethanol at a concentration of 0.5 mg / ml; 3) Spin coating the perovskite film. Before spin coating the perovskite film, filter the dissolved perovskite precursor solution with a 0.2 μm PTFE filter; The prepared perovskite precursor solution was spin-coated on the substrate using a multi-step spin-coating mode. In the first step, the rotation speed was adjusted to 1000rpm / s and the spin coating was performed for 10s. In the second step, the rotation speed was 5000rpm / s and the spin coating was performed for 40s. During the second step of spin coating, 250μL of anti-solvent chlorobenzene was added using a pipette when there were 10s of spin coating time left. After the spin coating was completed, the solution was annealed on a heating table at 100°C for 30min. The perovskite precursor solution was prepared by dissolving a certain amount of PbI2, PbBr2, FAI, MAI and CsI into a mixed solution of DMF and DMSO, and the molar ratio of each component was (PbI2+PbBr2): FAI: MAI: CsI was 1.7115:1.3855:0.163:0.0815. Then, 9mol% of MACl was added as an additive. The solution was then rotated and stirred until the drug was completely dissolved to obtain a perovskite precursor solution. 4) Prepare the PCBM electron transport layer by spin coating at a speed of 1500 rpm / s and a spin coating time of 30 seconds. Then heat at 100°C for 5 minutes. The solution preparation method of the PCBM electron transport layer is as follows: dissolve the PCBM nanoparticles in 1 mL of chlorobenzene to a concentration of 20 mg / mL; 5) Spin coating to prepare the BCP interface modification layer, the rotation speed is 5000 rpm / s, the spin coating time is 30 s, and the dynamic spin coating method is adopted; then it is heated at 100°C for 3 min; wherein the solution preparation method of the BCP interface modification layer is: dissolving the BCP nanoparticles in isopropanol solution at a concentration of 0.5 mg / mL, and taking the upper clear liquid for use; 6) Evaporating a transparent electrode: first, slowly evaporate 1 nm of Au, Cu or Al at a speed of 0.01 nm / s as a nucleation induction layer, and then evaporate 7-16 nm of an ultra-thin Ag electrode layer at a speed of 0.05 nm / s.
8. The method for preparing a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer according to claim 1, characterized in that: The volume ratio of DMF:DMSO is 4:
1.
9. The method for preparing a semi-transparent perovskite solar cell based on a ternary cation perovskite light-absorbing layer according to claim 1, characterized in that: The concentration of the perovskite precursor solution is 1.63 M, with an excess of 5 mol% PbI2.
Citation Information
Patent Citations
Light absorption layer material of solar cell, ternary cation perovskite solar cell and preparation method of ternary cation perovskite solar cell
CN113130762A
Tin-based perovskite solar cell based on indene additive and preparation method thereof
CN114188485A
All-inorganic perovskite solar cell based on 2-amino-5-bromoacetophenone interface modification and preparation method thereof
CN119012730A
Method for preparing perovskite thin film and application thereof
WO2019148326A1
Perovskite material and application thereof in solar cell
WO2023184620A1